Meningkatkan Prestasi Belajar Konsep Dasar Upakara Yadnya Dalam Pendidikan Agama Hindu Dengan Pembelajaran Kooperatif STAD Siswa Kelas IV Semester I SD Negeri 3 Tista - I Ketut Sumertiada (Jayapangus Press, 2019)
This study aims to improve understanding of concepts through the Implementation of the Cooperative Type STAD Learning Model. This study is a classroom action research (CAR) which is designed through two cycles. The design of each cycle consists of the stages of planning, implementation, and evaluation. Each cycle is carried out in 3 times face to face in class and ends with a final cycle test. The subjects of this study were students in grade IV semester I of the 2016/2017 Year of Learning in SD Negeri 3 Tista, totaling 11 students. The data collected in this study is data about understanding basic concepts. Data understanding concepts are collected through quizzes at each meeting and concept understanding tests carried out at the end of the learning cycle. Furthermore, the collected data is analyzed before it is compiled into a report in the form of class action research. Implementation STAD type cooperative learning model can improve understanding, results and learning achievements of the basic concepts of Upakara yadnya fourth grade students of Semester I 2016/2017 Year of Learning SD Negeri 3 Tista. This can be seen from the average understanding of the basic concepts of Upakara Yadnya Hinduism Education by students in the first cycle has an average of 79.97 in the category of incomplete, but after learning Hinduism in the second cycle with the Cooperative learning model of fourth grade students has an average of 91.43 with a Completed category. The results of this study prove that the Cooperative learning model greatly influences the efforts of students to achieve achievement in learning the basic concepts of upakara in the education of Hinduism in SD Negeri 3 Tista.